2012
DOI: 10.2355/isijinternational.52.1266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Roll Surface Profile on Centerline Segregation in Soft Reduction Process

Abstract: This study investigates the effect of roll surface profile on the centerline segregation of the molten metal (bloom) being solidified in the soft reduction process, where the molten metal (bloom) thickness is reduced consecutively by a set of rolls. The roll surface profiles are convex and flat. Finite element analysis was performed to examine the variations in solidus line contour, the phase state across the bloom cross-section and stress state of the bloom in the mushy zone to the casting direction when high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…It can severely degrade material homogeneity and thus affect the final properties and performance of billet-based products. Macrosegregation is also known as the main cause of cup fracture during wire cord drawing due to the formation of martensite and carbide networks [1]. Macrosegregation cannot be eliminated entirely during heat treatment, so preventing it in the casting process is crucial [2].…”
Section: Introductionmentioning
confidence: 99%
“…It can severely degrade material homogeneity and thus affect the final properties and performance of billet-based products. Macrosegregation is also known as the main cause of cup fracture during wire cord drawing due to the formation of martensite and carbide networks [1]. Macrosegregation cannot be eliminated entirely during heat treatment, so preventing it in the casting process is crucial [2].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, because of the different trial conditions, the empirical SR amount was significantly different, for example the 7.5±1.5 mm for bloom thickness of 350 mm, 2) 1.54-6.41 mm for bloom thickness of 380 mm, 6) and 20-30 mm for bloom thickness of 400 mm. 9) Therefore, it is difficult to form common criteria from these industrial trail results only.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The principle of SR is to impose a reasonable reduction rate/ amount on the solidification end of the strand for compensating liquid core shrinkage and preventing the soluteenriched liquid flowing toward the center of the strand without creating internal cracks. 1,2,4) In bloom SR process, the reduction is usually executed by 6-10 withdrawal units which are arranged in the air cooling zone with intervals of 1.0-3.5 m. Therefore the reduction interface is discontinuous, and the SR amount is generally selected as the primary control parameter during the bloom SR process.…”
Section: Introductionmentioning
confidence: 99%
“…The industry application showed that shrinkage and segregation defects were improved obviously by using the convex roll. 25,26) Understandably, the void closure of HHR 2 should be also affected by the surface profile of roller. The aim of this paper is to design an appropriate roll profile especially for HHR 2 for eliminating the shrinkage cavities of bloom.…”
Section: Work Roll Surface Profile Design and Optimization For Hot-comentioning
confidence: 99%
“…Convex roll can form stress concentration at the middle zone of blooms, which promotes core deformation, and this was also mentioned in MOON Chang Ho's work. 26) Meanwhile the surface temperature of blooms was lower than the core, which amount to forming a hard shell outside the bloom, so the middle zone of blooms was unsubstantial because of the thinner shell. When the convex roll works, the combined action of hard shell and convex roll may form torque taking the corner of convex as the fulcrum.…”
Section: Effect Of Roll Surface Profiles On Void Closurementioning
confidence: 99%